Novel nanohybrids for effervescence enhanced magnetic solid‐phase microextraction of wide‐polarity organic pollutants in roasted meat samples. Issue 24 (28th October 2021) - Liu, Tingting; AgyeKum, Evans; Ma, Sai; Ye, Hanzhang; Li, Jiani; Gao, Ming; Ni, Min; Zhang, Xiaofan; Wang, Xuedong
Abstract: To simultaneously and efficiently extract pollutants with differential polarities, we herein fabricated and characterized a multifunctional nanocomposite. The novel nanohybrids used NiFe2 O4 as magnetic cores, and NH2 ‐MIL‐101(Al), β‐cyclodextrin and graphene oxide as functional components combined with magnetic cores. With the aid of graphene oxide's large π‐conjugated system, NH2 ‐MIL‐101(Al)'s strong adsorption to moderately/strongly polar chemicals, and β‐cyclodextrin's specific recognition effect, the nanohybrids realized synergistically efficient extraction of polyaromatic hydrocarbons and bisphenols with a log Kow range of 3–6. Combined with acidic and alkaline sources, the nanohybrids‐based effervescent tablets were prepared. Based on effervescent reaction‐enhanced nanohybrids‐based efficient adsorption/extraction and high performance liquid chromatography and fluorescence detection, we successfully developed an excellent microextraction method for the simultaneous determination of both polyaromatic hydrocarbons and bisphenols in roasted meat samples. Several important variables were optimized as follows: Na2 CO3 and tartaric acid as acidic and alkaline sources, 900 μLof the mixed solvent (acetone and hexane at 2:1 by v/v) as the eluent, 5 min of elution time. Under optimized conditions, the novel method gave low limits of detection (0.07–0.30 μg kg −1 ), satisfactory recoveries (86.9–103.9%), and high precision (relative standard deviations of 1.9–6.7%) in roasted lamb, beef, pork, chicken, and sausage samples.